Peusijuek Ritual in the Perspectives of Local Acehnese Cultural Wisdom Education - Ridwan, Ridwan; Manan, Abdul (Universitas Tanjungpura, 2025)
This study aims to analyze the educational values and symbolic meanings in the peusijuek ritual. This study uses a qualitative descriptive method with research instruments; meticulous observation and in-depth interviews with religious figures, traditional figures, and youths. The results of the study indicate that the educational value in the peusijuek ritual is a medium for gluing social relations, resolving disputes, strengthening kinship, and integrating the interests of the Acehnese people, as well as a medium for controlling balance and inner satisfaction in community relations. Symbolic meanings in the peusijuek ritual are; first, the general meaning of the material symbol in the form of the material used implies the transfer of the nature of objects to humans in the peusijuek ritual as a sign of gratitude, sharing happiness, and strengthening success. Second, the special meaning of the place where the betel is placed is like the earth of God, sticky rice as a glue, candied coconut as a sweetener, rice and paddy symbolize prosperity, plain flour mixed with water symbolizes coolness, a bundle of leaves symbolizes harmony in one bundle, a basin symbolizes income, and a food cover is like the sky that covers the earth.